Branching of lung epithelium in vitro occurs in the absence of endothelial cells. Issue 4 (28th January 2015) - Havrilak, Jamie A.; Shannon, John M.
Abstract : Background: Early lung morphogenesis is driven by tissue interactions. Signals from the lung mesenchyme drive epithelial morphogenesis, but which individual mesenchymal cell types are influencing early epithelial branching and differentiation remains unclear. It has been shown that endothelial cells are involved in epithelial repair and regeneration in the adult lung, and they may also play a role in driving early lung epithelial branching. These data, in combination with evidence that endothelial cells influence early morphogenetic events in the liver and pancreas, led us to hypothesize that endothelial cells are necessary for early lung epithelial branching.Results: We blocked vascular endothelial growth factor (VEGF) signaling in embryonic day (E) 12.5 lung explants with three different VEGF receptor inhibitors (SU5416, Ki8751, and KRN633) and found that in all cases the epithelium was able to branch despite the loss of endothelial cells. Furthermore, we found that distal lung mesenchyme depleted of endothelial cells retained its ability to induce terminal branching when recombined with isolated distal lung epithelium (LgE). Additionally, isolated E12.5 primary mouse lung endothelial cells, or human lung microvascular endothelial cells (HMVEC‐L), were not able to induce branching when recombined with LgE.Conclusions: Our observations support the conclusion that endothelial cells are not required for early lung branching. Developmental Dynamics 244:553–563, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: Endothelial cells are not required for terminal branching in cultured embryonic lung explants. Endothelial cells are not required for expression of lung epithelial cell marker genes. Endothelial cells are not sufficient to support growth and branching of embryonic lung endoderm.